PENGARUH KEDISIPLINAN DAN KREATIVITAS GURU TERHADAP MOTIVASI BELAJAR SISWA DI MI KECAMATAN PUNGGELAN BANJARNEGARA 2017/2018 - Fajar - Riyanto; Mustaqim -; Lutfan Muntaqo (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2019)
The purpose of the study was to determine the effect of discipline and creativity of teachers on student learning motivation in MI se Sub Punggelan Banjarnegara District. This research includes field type using quantitative approach where the analysis used is statistical analysis. Based on the analysis with the help of SPSS 16 program can be obtained constant equation of 22.569, teacher discipline coefficient of 0.304 and teacher creativity coefficient of 0.448. Thus the equation of the regression line is Y = 22,569 + 0,304X1 + 448X2. The equation of positive regression line indicates that the better the discipline and creativity of the teacher hence can improve student's learning motivation. Based on table model summary out put SPSS 16 computer above can be explained that obtained value Adjusted R Square of 0.433. It means that teacher discipline variable and teacher creativity influence to student learning motivation together equal to 43,30% and equal to 56,70% determined by other factor. So the conclusion there is influence of discipline and creativity of teacher to motivation learn student equal to 43,30% is significant, and can be generalized to entire population.